APPLICATION OF COOPERATIVE LEARNING METHODS WITH THINK PAIR AND SHARE MODEL ON-LINE TYPE TO IMPROVE STUDENT COOPERATION: PENERAPAN METODE PEMBELAJARAN KOOPERATIF MODEL THINK PAIR AND SHARE TIPE DALAM JARINGAN UNTUK MENINGKATKAN KERJASAMA SISWA - Moh. Sabab Nashrulloh (SOSIOEDUKASI, 2020)
The Think Pair and Shairecooperative (TPS)learning method is a learning method in the form of group discussions which is commonly applied in face-to-face learning. It is new if the TPS model of cooperative learning method is applied in a network that remembers the pandemic situation and in the new learning year at school. Where the cooperative method becomes a discussion method that makes the cooperation of students more active and can socialize among new students in particular. This condition is necessary and good for students to increase cooperation and the socialization process between school friends. This study uses observation methods in data collection and uses cycle description methods in data analysis. This research generates new knowledge that cooperative research methods can be carried out in networks and using the Think Pair and Shaire model can positively increase cooperation between students and create a space for socialization among new students in particular.